Enhancing work environments and reducing turnover intention: a multicenter longitudinal cohort study on differentiated nursing practices in Dutch hospitals - Julia van Kraaij; Neeltje de Vries; Hanna Wessel; Hester Vermeulen; Catharina van Oostveen; RN2Blend Consortium (BMC Nursing)
Abstract Background Addressing the growing challenge of nurse retention requires coordinated actions at national and global levels to improve recruitment, retention policies, and investments in the nursing work environment. The nursing work environment, defined as the "organizational characteristics of a work setting that facilitate or constrain professional nursing practice", is critical in influencing whether nurses decide to leave their jobs. This study investigates the impact of differentiated nursing practices – which involved tailoring roles and responsibilities based on nurses’ training, skills, and experience in Dutch hospitals – and investigated their impact on the nursing work environment and turnover intention (i.e., nurses’ intentions to leave their organization). We also explored whether the work environment mediates this relationship. Methods A multicenter longitudinal cohort study was conducted across 19 Dutch hospitals between 2019 and 2023. Nursing professionals participated via digital surveys administered before (T0) and after (T1) differentiated nursing practices were introduced. The nursing work environment was assessed using the Practice Environment Scale of the Nursing Work Index. A multilevel analysis with a random intercept and fixed slope was used to evaluate the impact of differentiated nursing practices on the work environment and on nurses' turnover intentions. Results We received 5411 responses to our questionnaire – 4259 at T0 and 1152 at T1. Results showed that, while the overall work environment improved, particularly in the dimensions of staffing and resource adequacy, collegial nurse–physician relationships, and participation in hospital affairs, there were no significant improvements in nursing foundation for quality of care or nurse managers' ability, leadership, and support of nurses. Additionally, differentiated nursing practices did not significantly impact turnover intention, nor did the work environment mediate this relationship. Conclusions This study is the first to explore the unique effects of practice differentiation on turnover intention mediated by the work environment. The findings suggest that, while differentiated practices can enhance certain aspects of the work environment, a more systemic and integrated approach is required for sustained improvements. Future research should include longer term studies to fully understand the complex relationship and accompanying mechanisms between differentiated nursing practices, the nursing work environment, and turnover intention. Trial registration Clinical trial number not applicable.